2021
DOI: 10.1038/s41598-021-03284-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of inter-farm transmission of highly pathogenic avian influenza H5N6 integrating vehicle movements and phylogenetic information

Abstract: Highly pathogenic avian influenza (HPAI) in poultry holdings commonly spreads through animal trade, and poultry production and health-associated vehicle (PPHaV) movement. To effectively control the spread of disease, it is essential that the contact structure via those movements among farms is thoroughly explored. However, few attempts have been made to scrutinize PPHaV movement compared to poultry trade. Therefore, our study aimed to elucidate the role of PPHaV movement on HPAI transmission. We performed netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…This is consistent with previous studies from around the world (Gilbert & Pfeiffer, 2012) and South Korea (An et al., 2021) indicating that high poultry density is a proxy of contact opportunities between farms including vehicle movements or networks between farmers and the increased poultry‐related activities, which can explain the increased likelihood of HPAI H5N6 infections in the study area (Bonney et al., 2018; Liang et al., 2020; Walsh et al., 2020). Given the findings of a previous study in South Korea (Yoo et al., 2021), which estimated that vehicle movements were responsible for approximately 30% of HPAI H5N6 infections, the identified estimates of poultry density would be interpreted as the associations with the increased poultry‐related activities, including biosecurity breakdowns associated with indirect contacts with HPAIV from wild birds and the sharing of farm inputs such as personnel, feed, and water resources, thereby facilitating the introduction of HPAIV into a farm. In light of the challenges in limiting the establishment of poultry farms in regions where poultry production is in great demand, it is essential to improve farm‐level biosecurity to reduce the risk of HPAI infection of poultry farms already located in the region (Liang et al., 2020).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This is consistent with previous studies from around the world (Gilbert & Pfeiffer, 2012) and South Korea (An et al., 2021) indicating that high poultry density is a proxy of contact opportunities between farms including vehicle movements or networks between farmers and the increased poultry‐related activities, which can explain the increased likelihood of HPAI H5N6 infections in the study area (Bonney et al., 2018; Liang et al., 2020; Walsh et al., 2020). Given the findings of a previous study in South Korea (Yoo et al., 2021), which estimated that vehicle movements were responsible for approximately 30% of HPAI H5N6 infections, the identified estimates of poultry density would be interpreted as the associations with the increased poultry‐related activities, including biosecurity breakdowns associated with indirect contacts with HPAIV from wild birds and the sharing of farm inputs such as personnel, feed, and water resources, thereby facilitating the introduction of HPAIV into a farm. In light of the challenges in limiting the establishment of poultry farms in regions where poultry production is in great demand, it is essential to improve farm‐level biosecurity to reduce the risk of HPAI infection of poultry farms already located in the region (Liang et al., 2020).…”
Section: Discussionmentioning
confidence: 94%
“…However, we considered that the variables including the poultry density and poultry species variables and the spatial effects of the model could partly reflect the effects of network of the livestock-related vehicles. Moreover, given that 30% of the HPAI occurrence was contributed by the vehicles (Yoo et al, 2021), it can be considered that our analysis would demonstrate the epidemiology of HPAI.…”
Section: Discussionmentioning
confidence: 99%
“…The acquisition of the same plasmids in different hosts and/or farms might suggest a common environmental compartment that is shared by different farms (e.g., water), other unknown indirect transmission routes [64] or plasmid transmission into the hosts' bacterial flora during transient gut colonization [65]. An alternative explanation of plasmid sharing in multiple farms could be the movement of people and animals between farms colonized with these bacteria and/or plasmids, as observed for other microorganisms [66][67][68]. A recent study highlighting the Thai pig trade network indicated that this network could facilitate the spread of infectious diseases [69].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research studies have highlighted the dynamic behavior of HPAI virus spread, along with the variables that affect the radius of bird culling around the infected zone during the local transmission of avian influenza viruses, although there was a disparity in focusing on the areas that are at high risk. It is crucial to assess high-risk sites based on prior HPAI H5N8 epidemics [ 25 , 26 ]. Inverse distance weighting and kriging approaches were used to predict high-risk locations in South Korea.…”
Section: Introductionmentioning
confidence: 99%